Neoliberalism Violence in the Production of Tourist Spaces: A Perspective from Macaneta Beach – Mozambique - Lucas Atanasio Catsossa; Bruno Ferreira Campos; Edvaldo Cesar Moretti (Via@, 2024)
This study investigates and discusses the detrimental impacts of neoliberalism on the Macaneta Beach tourist destination. Methods used for this analysis include a literature review coupled with field research carried out during the “Social practices and women and men knowledge and the production of the rural territory in the Marracuene district in Mozambique: the viability of the productive alternatives in the world of the sustainability” project, supported by CAPES/AULP (2014, 2015). This research determined that Macaneta Beach has been formed and is controlled by capitalist interests. The site’s transformation has resulted in both tangible acts of violence and violations, expressed via territorial segregation, and the subordination of local individuals to international economic entities promoting tourism. These developments have inhibited the proliferation of benefits and opportunities based on the local lifestyles of the Macaneta Beach inhabitants.